Investment and uncertainty in a quadratic adjustment cost model: Evidence from Brazil - Rodrigo Mendes Pereira (Institute for Applied Economic Research (ipea), 2015)
In this paper I assess empirically the sign of the uncertainty-investment relation in Brazil within a quadratic adjustment cost model. It is shown that these variables are negatively related in the Brazilian economy. The implication is that investment can be enlarged with the adoption of a sustainable macroeconomic policy that rules out uncertainty-yielding shocks, like huge devaluation in domestic currency, or defaults in internal and external debts. I also propose a method for estimating the quadratic adjustment cost model when the endogenous variable is I(2) and the forcing variables are I(1). As long as capital stock is typically an I(2) variable, the econometric insight seems particularly suited for models of investment.
Keywords: 330